Wildlife Conflict and Prevention Strategies Adopted by Farmers and Forest Officials - Meena, Deepak Chand; Meena, B. S.; Sankhala, Gopal; Garai, Sanchita; Meena, H. R.; Latha C., Madhu (Indian Journal of Extension Education, 2023)
Human-wildlife conflict is unfavorable interactions between people and wild animals that hurt both people and their resources as well as wildlife and their habitats. The study was conducted in the year 2021-2022 in the surrounding villages of Ranthambore Tiger Reserve to understand the type of conflict and strategies adopted to prevent conflict. Garret ranking method was used to assess degree of vulnerability of crops and livestock towards wild animals and vice versa and strategies to prevent conflict. Farmers have grown 10 types of crops among them maize and among livestock goat was highly preferred by wild animals. Farmers mostly followed seven strategies to prevent conflict out of seven, fencing around the field and guarding crops and livestock by humans was found most effective strategies and eight practices were followed by forest officials to prevent conflict out of eight, boundary wall around the reserve area was most effective practice.
Keywords: Crops; Farmers; Human wildlife conflict; Livestock; Strategies; Wild animals